Relación entre la asertividad de los padres de familia y las habilidades sociales de los niños de 5 años de la I.E Inicial N°303 Santa Rosa de Enace - Vásquez Panduro, Sonia Zelicet (2011)
The present work of lnvestigation developed with the aim to determine the relation that exists between the Asertividad of the Family parents and the Social Skills of the 5-year-old children of the Educational lnitial lnstitution N o 303 - Sector Santa Rosa of Enace, of the district of Rioja in the year 2010. The investigation with which the work of investigation was designad was of the type correlaciona!, and of the explanatory partial level. One worked with a sample of 15 children and 15 parents. By means of the technology of the survey; there was gathered information of the asertividad of the parents, applying a scale of asertividad. Across the interview; there was applied the questionnaire of social skills to the children. The gathered information was processed by means of the distribution of frequencies and Pearson's coefficient. Accused and analyzed the information and results, brings over of the score of the questionnaires: levels of asertividad that possess the Parents of Family and the levels of social skills that the children possess, one affirms that it is more frequent parents and children find with a high leve! of asertividad and social skills. The average score of the level of asertividad is 17,00 points (high leve/ of asertividad) and the average score of the level of social skills is 19,13 (high · leve/ of social skills). The standard diversion shows the dispersion of the average scores about his average and is observed in the level of asertividad the dispersion of from 3,07 a homogeneous population (18,06% of coefficient of variation), and in the leve! of social skills the dispersion is 2,03 that it comes from a population also very homogeneous and is demonstrated in the result of the coefficient of variation (10,61 %).